A fermion in a scalar inversely linear potential - de Castro, A. S. (American Institute of Physics (AIP), 2004)
The problem of a fermion subject to a a scalar inversely linear potential in a two-dimensional world is mapped into a Sturm-Liouville problem for nonzero eigenenergies. This mapping gives rise to an effective Kratzer potential and exact bounded solutions are found in closed form. The normalizable zero-eigenmode solution is also found. A few unusual results are revealed.